Sural Island Flap A Good Option for Coverage of the Exposed Heel (Tendo-Achillis) (Journal of Dhaka Medical College, 2010)
A prospective observational study was carried out in DMCH and some other private clinics in Dhaka from January 2008 to March 2010. A total of 15 patients with exposed Tendo-Achillis with or without tendon injury were taken in this study . M:F= 13:2. Age range was 18- 45 years. In 13 cases Tendo-achillis (TA) were cut and repaired in emergency department of DMCH and other Hospitals followed by loss of skin over the TA. In 2 cases skin over the TA were lost due to direct trauma. Mode of injury was cut injury in toilet pan 9(59.99%), RTA 4(26.66 %) and direct cut injury without tendon injury 2 (13.33%).All the patients were treated with surgical toileting after admission and wound were covered by distally based sural island flap .Average follow up period was 36 weeks. Flap coverage were done within 5 days to 25 days from the day of injury. Outcome was evaluated by flap vascularity and skin colour .Majority of the patients were returned to normal activity after 20 weeks of operation. The purpose of the study was to find out the way of coverage of the exposed TA(Tendo-Achillis) by orthopaedic surgeons without any special training. Key words: Sural Island Flap; Repair of Tendo-Achillis. DOI: 10.3329/jdmc.v19i1.6246 J Dhaka Med. Coll. 2010; 19(1) : 19-24.